“For the sake of the child”: establishing harmonised standard regulations for Malaysians in addressing issues relating to the international parental child abduction - Che Soh @ Yusoff, Roslina; Ibrahim, Norliah (Centre for Islamisation (CENTRIS), IIUM, 2024)
In recent years, there has been a notable increase in cases of parental child abduction on a global scale. It is not uncommon for custody battles between estranged parents to result in the noncustodial parent absconding with the child, leaving no trace. In some instances, the abducted child may be taken to another country by the non-custodial parent in order to evade detection and avoid punishment. This can have a detrimental effect on the child's long-term interests, particularly with regard to maintaining access to both parents. International efforts have been made to address this complex issue. The United Nations Convention on the Rights of the Child classifies parental child abduction as a crime, while the Hague Convention on Parental Child Abduction was created to resolve disputes related to court jurisdiction in determining the appropriate forum for such cases. Despite the fact that Malaysian civil law criminalises parental child abduction, it has not proven to be an effective tool in combating the problem, particularly in cases involving international parental child abduction, due to the fact that Malaysia is not a signatory to the Hague Convention. This paper seeks to examine the position of parental child abduction under Malaysian civil and Shari’ah laws, as well as the approach of the courts in dealing with such cases, especially those involving international parental child abduction. The paper also considers the implications of Malaysia adopting the Hague Convention in order to comply with international standards when addressing parental abduction, as well as the potential effects on the child's interests. Ultimately, the paper aims to propose a more effective solution by establishing harmonised standard regulations that can provide children with feasible protection against this problem, particularly in cases of international parental child abduction. By utilising a doctrinal methodology to arrive at its findings, the paper suggested that there should be a bilateral agreement between the countries affected besides establishing harmonised standard regulations for Malaysia in addressing international parental child abduction in protecting children's rights and welfare.